Technological characteristics of the fibre of vicuñas in semi-captivity of the Multicommunal Picotani - Puno region - Quispe Coaquira, Jesús E. (2018)
The aim of this study was to determine staple and fibre length, as well as the fibre diameter of vicuñas by age (cria, juvenile and adults) and sex (male and female). The study was carried out in the semicaptivity vicuña farm of Multicomunal Picotani, Puno, Peru, located between 4420 and 4800 m above the sea level. Response variables were analyzed in a factorial arrangement of 2x3 conducted in a completely radomized design. The mean staple length was 3.03 ± 0.52 and 2.97 ± 0.51 cm for males and females (p>0.05) and 3.08 ± 0.47, 3.33 ± 0.39 and 2.59 ± 0.39 cm for crias, juveniles and adults respectively (p<0.05). The fibre length was 4.13 ± 0.53 and 4.06 ± 0.55 cm in males and females (p>0.05) and 4.22 ± 0.28, 4.57 ± 0.27 and 3.50 ± 0.34 cm for crias, juveniles and adults respectively (p<0.05). The fibre diameter was 12.755 ± 0.580 and 12.719 ± 0.398 ìm for males and females (P>0.05), and 12.359 ± 0.352, 12.856 ± 0.442 and 12.997 ± 0.447 μm for juveniles and adults, respectively (p<0.05). The variables in the study did not show significant differences for the sex factor, while the juvenile vicuñas recorded the greatest staple and fibre length, and the crias had the greatest fineness (p<0.05).